Management of Adenocalymna impressum on pasture in the northwestern Mato Grosso - Horn, Ricardo; Yamashita, Oscar Mitsuo; Ferreira, Aureane Cristina Teixeira; Carvalho, Marco Antonio Camillo de; Dallacort, Rivanildo; Felito, Ricardo Adriano; Rocha, Adriano Maltezo da; Teixeira, Soraia Olivastro; Batistão, Alan Carlos; Parente, Tiago de Lisboa; Caioni, Sheila (Revista de Ciências Agro-Ambientais, 2017)
The occurrence of weeds in pastures is a factor that represents a loss of productivity because they compete directly with the essential elements and space with the forage. We aimed with this study was to evaluate the chemical control of Adenocalymna impressum with experiments conducted in the municipality of Juruena, Mato Grosso. Control techniques evaluated were: fluroxypyr + aminopyralid in adult plant; (fluroxypyr + aminopyralid) + (triclopyr) in adult plant; fluroxypyr + aminopyralid on regrowth; (fluroxypyr + aminopyralid) + (triclopyr)on regrowth; (picloram + triclopyr) basal; (picloram + triclopyr) on stump (after mowing). The experiment was conducted in a randomized block design with four replications. We give phytotoxicity notes from 0 to 100, where 100 means death of the plant, we also evaluated phytotoxicity of foliar herbicides on Brachiaria brizantha cv. ‘Marandu’. The evaluations were performed at 10, 20, 30, 60, 90, 120 and 150 days after application. The data were submitted to analysis of variance and means were compared by Tukey`s test at 5% probability, using the SISVAR program. All treatments showed weed control, but only the herbicide picloram + triclopyreffectively controlled A. Impressum. Damage of foliar herbicides on B. brizantha was temporary, it recovered on 3rd assessment.